Deregulation of shopping hours: The impact on independent retailers and chain stores - Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2010)
This paper studies shopping hour decisions by retail chains and independent competitors. We use a Salop-type model where retailers compete in prices and shopping hours. Our results depend significantly on efficiency differences between retail chain and independent retailer. If the efficiency difference is small, the independent retailer may choose longer shopping hours than the retail chain and may gain from deregulation at the expense of the retail chain. The opposite result emerges when the efficiency difference is large. Then, the retail chain may benefit whereas the independent retailer loses from deregulation.
Keywords: L13; L51; L81; 330; business hours; retailing; deregulation; Öffnungszeit; Deregulierung; Einzelhandel; Potenzieller Wettbewerb